Changes in discourse structure over time following traumatic brain injury. (October 2018) - Lindsey, André; Mozeiko, Jennifer; Krueger, Frank; Grafman, Jordan; Coelho, Carl
Abstract: The objective of the present study was to investigate structural changes in the narrative discourse of individuals with penetrating traumatic brain injury (pTBI) following immediate and delayed story retellings. Additionally, the potential influence of immediate memory, working memory, and executive functions on narrative discourse performance were examined. The narrative discourse of two groups, 123 with pTBI and 44 non-brain injured (NBI), was sampled. Participants were asked to retell a wordless picture story immediately after viewing it and again 30-min later. Story narratives were analyzed using a variety of microlinguistic and macrostructural measures. Results revealed significant group differences of both microlinguistic and macrostructural measures following the immediate retell, but not following the delayed retell. Regression analyses revealed that immediate memory accounted for a modest degree of the explained variance for the production of critical content during narrative discourse. The observed deficits were relatively stable over a short delay (30 min) and appeared attributable, in part, to difficulty with the encoding and consolidation of story content. Highlights: Traumatic brain injury can result in discourse deficits. Discourse deficits reflect disruptions to cognitive-linguistic processing. Discourse deficits are observed at both microlinguistic and macrostructural levels. Immediate memory influences critical content production during narrative discourse. Encoding and memory consolidation appear linked to critical content production.